2017
DOI: 10.1590/1678-4499.627
|View full text |Cite
|
Sign up to set email alerts
|

Early performance of ‘Kampai’ and ‘Rubimel’ peach on 3 training systems

Abstract: Received: Dec. 11, 2015 -Accepted: Mar. 28, 2016 production per tree, fruit weight, yield, fruit firmness, and soluble solids. The early yield and economic return are greater in Central Leader training system for both cultivars. Besides, training system does not influence fruit quality attributes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…The peaches of the LC -trained trees presented greater values in mass, diameter and fruit polar diameter in relation to the fruits from trees trained in the other systems, due to the prioritization of tree structure formation in the first year in the LC system, which has a higher source/sink relation, allowing greater growth. Mayer et al (2016) and Pasa et al (2017) found no significant changes in the fresh mass and size of peach fruit in the training systems used. However, Miller and Scorza (2002) found higher values in the fresh mass and fruit size of CL-trained trees.…”
Section: Resultsmentioning
confidence: 92%
“…The peaches of the LC -trained trees presented greater values in mass, diameter and fruit polar diameter in relation to the fruits from trees trained in the other systems, due to the prioritization of tree structure formation in the first year in the LC system, which has a higher source/sink relation, allowing greater growth. Mayer et al (2016) and Pasa et al (2017) found no significant changes in the fresh mass and size of peach fruit in the training systems used. However, Miller and Scorza (2002) found higher values in the fresh mass and fruit size of CL-trained trees.…”
Section: Resultsmentioning
confidence: 92%
“…Considering the Central Leader, this latter study obtained 7.77 t ha -1 and 9.57 t ha -1 (two-years old) and 14.41 t ha -1 and 11.87 t ha -1 (three-years old), respectively for 'Kampai' and 'Rubimel' cultivars (Pasa et al, 2017). However, considering the Ypsilon the yields were 4.39, 4.35, 3.27 and 5.22 t ha -1 , respectively for 'Kampai' and 'Rubimel' cultivars at two-and three-years old (Pasa et al, 2017).…”
Section: Discussionmentioning
confidence: 72%
“…These results show that despite the lower number of plants per ha, the trees from Fruiting Wall have high capability of fruit set, in addition to the highest mass per fruit. Similarly, Pasa et al (2017) present the highest values for yield by tree for the Central Leader, with 7.77 and 14.41 kg tree -1 (cv. 'Kampai'), and 9.57 and 11.87 kg tree -1 (cv.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations